THE TIMING OF INITIATION OF FAST-FLOWING ICE STREAMS DURING A GLACIAL CYCLE INFERRED FROM GLACIMARINE SEDIMENTATION - Dowdeswell J.A.; Elverhoi A. (My University, 2002)
Fast-flowing ice streams drain huge basins within modern ice sheets and are a mechanism for rapid iceberg production and mass loss. Some ice streams are known to be unstable, and to switch between fast flow and stagnation. Numerical ice-sheet models and geophysical observations of large-scale streamlined glacial landforms and large glacier-derived sedimentary fans along high-latitude continental margins indicate the presence of ice streams in Quaternary ice sheets. High-resolution AMS dated sedimentary records from an inter-fan area on the Svalbard continental margin yield evidence on the timing of initiation of fast glacier flow during a glacial cycle of ice-sheet growth and decay. Sedimentation rates and iceberg-rafted debris influx show that debris delivery to the Svalbard margin was relatively high during the period of Late Weichselian ice-sheet growth from about 30#000-18#000 yr BP. Both parameters fell dramatically in inter-fan areas when full-glacial conditions, with ice at the continental shelf edge, were established at about 18#000 yr BP. This shift is interpreted to mark the initiation of a fast-flowing ice stream, the convergence of flow from the surrounding ice sheet into this ice stream, and the consequent slowing of ice flow and sediment delivery to the inter-fan area beyond the ice-stream margins. This provides a constraint on the timing of ice-stream initiation during the cycle of ice-sheet growth and decay.
Keywords: ICE STREAMS; FAST GLACIER FLOW; GLACIAL CYCLES; SUBMARINE FANS; SVALBARD MARGIN; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная